The Progress and Challenges of Implementing HLA Molecular Matching in Clinical Practice - Suzanne Bezstarosti; Sebastiaan Heidt (Transplant International)
HLA molecular matching in solid organ transplantation in the form of eplets, solvent-accessible amino acids or PIRCHE-II has been proposed as a more granular method than HLA matching on the antigen level. While many studies have shown the association between molecular mismatches and de novo donor-specific antibody formation, rejection and graft loss, evidence for prospective molecular matching in allocation is currently lacking, and the actual practical implementation and feasibility of molecular matching remains unclear. In this review the various potential applications of molecular matching in transplantation are discussed, including 1) organ allocation in deceased donor programs, 2) living donor selection, 3) increasing the transplantability of highly sensitized patients and 4) risk stratification to facilitate personalized immunosuppressive management, along with the challenges and gaps in current knowledge regarding these approaches. While clinical application of molecular mismatch analysis in solid organ transplantation holds promise, the fundamentals of HLA-specific antibody biology and epitope-paratope interactions should be further elucidated. This will aid in unraveling the factors that affect the relative immunogenicity of HLA molecular mismatches in order to start using molecular matching in clinical transplantation.